2011
DOI: 10.1212/wnl.0b013e31821ccd18
|View full text |Cite
|
Sign up to set email alerts
|

Final results from 18 years of the International Lamotrigine Pregnancy Registry

Abstract: The Registry did not detect an appreciable increase in MCM frequency following first-trimester lamotrigine monotherapy exposure. With over 1,500 first-trimester monotherapy exposures, the Registry was powered to detect major teratogenicity. The proportion of infants with MCMs following lamotrigine/valproate polytherapy exposure was high, but similar to that previously reported with valproate monotherapy. The Registry failed to observe an increased MCM frequency with increasing lamotrigine dose. Monitoring of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 20 publications
4
83
0
3
Order By: Relevance
“…The International Lamotrigine Pregnancy Registry has published 414 first trimester monotherapy exposures to lamotrigine, 12 MCMs (2.9%; 95% CI: 1.6-5.1%) were observed. No pattern of malformation was observed in any group [14]. The UK Epilepsy and Pregnancy Register has reported very similar results with MCMs in 3.2% (95% CI: 2.1-4.9%) of 647 children [10].…”
Section: Preconceptual Counselingmentioning
confidence: 81%
See 3 more Smart Citations
“…The International Lamotrigine Pregnancy Registry has published 414 first trimester monotherapy exposures to lamotrigine, 12 MCMs (2.9%; 95% CI: 1.6-5.1%) were observed. No pattern of malformation was observed in any group [14]. The UK Epilepsy and Pregnancy Register has reported very similar results with MCMs in 3.2% (95% CI: 2.1-4.9%) of 647 children [10].…”
Section: Preconceptual Counselingmentioning
confidence: 81%
“…Data reported from the International Lamotrigine Pregnancy Registry showed that, among 150 pregnancies exposed to polytherapy including sodium valproate in the first trimester, 16 MCMs (10.7%; 95% CI: 6.4-17.0%) were observed. In comparison, among 430 pregnancies exposed to polytherapy including lamotrigine but not sodium valproate, only 12 MCMs (2.8%; 95% CI: 1.5-5.0%) were recorded [14].…”
Section: Preconceptual Counselingmentioning
confidence: 93%
See 2 more Smart Citations
“…In most studies to date, it has been reported to be less hazardous than other AEDs. [64][65][66] Women of reproductive age who use lamotrigine have been shown to be less likely to have an unplanned pregnancy, and, if pregnant, appear to have an increased protection against bipolar depression. 67 Use of the drug is associated with congenital malformations, with a most common rate of 2%-3% reported.…”
mentioning
confidence: 99%